Navigating Employee Burnout in the Banking Sector: The Interplay of Emotional Intelligence and Organizational Support at Bank Sulselbar Masamba Branch - Serli Yandiani; S. Saharuddin; I Ketut Patra (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of emotional intelligence and organizational support on employee burnout at Bank Sulselbar, Masamba Branch. Utilizing a quantitative approach with a causal associative design, data were collected through structured questionnaires distributed to a total population of 36 employees. Due to the limited population size, a saturated sampling (census) technique was applied. Data analysis was conducted using Multiple Linear Regression through SPSS software version 30. The partial statistical results indicate that both emotional intelligence (t = -1.827; sig. 0.077 > 0.05) and organizational support (t = -1.214; sig. 0.233 > 0.05) have a negative but non-significant influence on employee burnout. However, the simultaneous testing (F-test) reveals that both variables collectively exert a significant effect on mitigating burnout, with a significance value of 0.016 < 0.05. The R-Square value of 0.220 indicates that the independent variables contribute 22% to the variance in employee burnout, while the remaining 78% is explained by other factors outside this research model. This study concludes that while internal psychological traits and external managerial resources are insufficient to reduce burnout independently, their integration acts as a critical strategic buffer against work exhaustion in the banking sector. Implications: Bank management is highly recommended to synergize specialized emotional coping training with structural organizational support, such as adjusting work demands and introducing psychological assistance programs, to effectively lower burnout levels.